(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Pallava Dynasty was a pastoral tribe who ruled thesouthern parts of India for almost 500 years. Pallava dynasty conquered theregion of Thondaimandalam that was located at Pallavapuri, The Pallava rulersestablished their kingdom on the ruins of the eastern part of the kingdom ofthe Satvahanas. They originally worked as officials under the Satvahana rulers,in the course of time they established themselves as local rulers. Very rapidlytheir kingdom spanned parts of southern Andhra Pradesh and northern Tamil Nadu.Pallavas established their capital at Kanchi which gradually became popular andfamous for its temples and as center of Vedic learning.